Respuesta :
[tex]x^2+5x-2=x+1\\
x^2+4x-3=0\\
x^2+4x+4-7=0\\
(x+2)^2=7\\
x+2=-\sqrt7 \vee x+2=\sqrt7\\
x=-2-\sqrt7 \vee x=-2+\sqrt7[/tex]
Answer:
common points will be [(-2+√7), (-1 + √7)] and [(-2-√7), (-1 -√7)]
Step-by-step explanation:
we have to find the point at which the equations are equal.
y = x² + 5x - 2 and y = x + 1
Now we Equate both the equations the point of intersections of both the equations
x² + 5x - 2 = x + 1
x² + 5x - x - 2 = 1
x² + 4x = 1 + 2
x² + 4x = 3
x² + 4x + 4 = 3 + 4
(x + 2)² = 7
x + 2 = ±√7
x = -2 ± √7
Since y = x + 1
Therefore, y = (-2 ± √7) + 1
y = -1 ± √7
Therefore, common points will be [(-2+√7), (-1 + √7)] and [(-2-√7), (-1 -√7)]